Ambivalence and Its Influence on Participation in Screening for Colorectal Cancer. (September 2013) - Oster, Candice; Zajac, Ian; Flight, Ingrid; Hart, Elizabeth; Young, Graeme P.; Wilson, Carlene; Turnbull, Deborah
Colorectal cancer (CRC) is one of the most prevalent cancers worldwide, and an ideal target for early detection and prevention through cancer screening. Unfortunately, rates of participation in screening are less than adequate. In this article we explore why people who were offered a fecal immunochemical test for CRC decided to participate or not, and for those who did participate, what influenced them to take action and complete the test. We conducted four focus groups and 30 telephone interviews with 63 people. The main reason people decided to screen was "wanting to know" their CRC status, which operated on a continuum ranging from wanting to know, through varying degrees of ambivalence, to not wanting to know. The majority of participants expressed ambivalence about CRC screening, and the main cue to action was the opportunity to screen without being too inconvenienced.